2014
DOI: 10.1016/j.aller.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical and allergological characteristics of Eosinophilic Esophagitis in a Spanish central region

Abstract: Our findings support those reported in the literature: the disease is more common in men aged 30-40 years with at least a three-year history of symptoms of esophageal dysfunction, sensitized to pollens, the predominant aeroallergen in our area, but also to plant foods or panallergens. These results increase the evidence for an immunoallergic aetiology and can help us in the early diagnosis of EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
3
23
0
1
Order By: Relevance
“…A higher prevalence of sensitization to food extracts has been detected by ImmunoCAP than by skin prick testing in both adults and children [9,27]. A similar situation was observed in our series ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A higher prevalence of sensitization to food extracts has been detected by ImmunoCAP than by skin prick testing in both adults and children [9,27]. A similar situation was observed in our series ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…The demographic characteristics of the series of children and adolescents with EoE described in this study match those reported by other authors [9,12]. EoE is more common in white males and in our series it was much more common in those who lived in an urban rather than a rural area.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6 In our patient, the EoE did not subside with high doses of IBPs, and, after explaining to him the possible treatments (corticosteroids or diet), he chose the elimination diet. 7 Since results of allergy testing against the most frequently involved foods were negative, the patient was prescribed a 6FED.…”
Section: Discussionmentioning
confidence: 65%
“…There were no randomized studies. One article was a case report, 33 two were case series, 30,34 one was a cross sectional study, 35 nine were case-control, 36-44 and six were cohort studies. 45-50 All articles were written in the last decade, with the earliest published in 2007.…”
Section: Resultsmentioning
confidence: 99%